Anorexia Nervosa Focal psychodynamic psychotherapy - Friederich, Hans-Christoph 1971-; Wild, Beate 1968-; Zipfel, Stephan 1962-; Schauenburg, Henning 1954-; Herzog, Wolfgang 1953- (Hogrefe Publishing, 2019)
This manual presents an evidence-based focal psychodynamic approach for the outpatient treatment of adults with anorexia nerrvosa, which has been shown to produce lasting changes for patients. The reader first gains a thorough understanding of the general models and theories of anorexia nervosa. The book then describes in detail a three-phase treatment using focal psychodynamic psychotherapy. It provides extensive hands-on tips, including precise assessment of psychodynamic themes and structures using the Operationalized Psychodynamic Diagnosis, real-life case studies, and clinical pearls. Clinicians also learn how to identify and treat typical ego structural deficits in the areas of affect experience and differentiation, impulse control, self-worth regulation, and body perception. Two detailed case vignettes provide deepened insight into the therapeutic process. A final chapter explores the extensive empirical studies on which this manual is based, in particular the renowned multicenter ANTOP study. Printable tools in the appendices can be used in daily practice. This book is of interest to clinical psychologists, psychotherapists, psychiatrists, counsellors, and students.